ANALISIS KESULITAN DALAM MEMECAHKAN MASALAH MATEMATIKA PADA SISWA KELAS VIII SMP UNGGULAN AL-FALAH PACUL BOJONEGORO - Siti Khusnul Khotimah; Dian Ratna Puspananda; Ayu Fitrianingsih (Journal of Technology, Mathematics and Social Science, 2022)
Abstrak:This study aims to find out how the students' difficulties in solving mathematical problems with the Circle material. There are several steps in solving math problems. According to Polya in Nur (2018) there are four steps in solving mathematical problems, namely (1) understanding the problem (understanding the problem); (2) plan problem solving (devising a plan); (3) planning problem solving (carrying out the plan); (4) Re-examine the solutions obtained (looking back). This research method is qualitative by using a qualitative descriptive approach. The population of this study was the eighth grade student of Al-Falah Pacul Bojonegoro with a total of 16 students. Collecting data using the method of observation, test questions, interviews and documentation. The technique of taking the subject in this study was purposive sampling, namely there were 12 subjects. The results of this study indicate that there are 4 students who meet the polya step and 11 students who do not meet the polya step in class VIII students of SMP Al-Falah Pacul Bojonegoro.Keywords: Difficulty Analysis, Problem Solving.